2020
DOI: 10.3389/fmicb.2020.01187
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Plasmid pSN1216-29 Host Range and the Similarity in Oligonucleotide Composition Between Plasmid and Host Chromosomes

Abstract: Strain or plasmidRelevant characteristics References Bacterial strains Escherichia coliDH5α F − , 80dlacZ M15, (lacZYA-argF) U169, deoR, recA1, endA1, hsdR17(r K − , m K + ), phoA, supE44, λ − , thi-1, gyrA96, relA1DH5α, Tc r This study S17-1 λpir RK2 tra regulon; host for pir-dependent plasmids; recA thi pro hsdR M RP4-2-Tc:Mu-Km:Tn7λpir Tp r Sm r Simon et al., 1983 Pseudomonas putida KT2440 pWW0-free Pseudomonas putida mt-2 Bagdasarian et al., 1981 KT2440(pBBR1MCS-5) pBBR1MCS-5-harboring KT2440 This study KT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…A mini-Tn 5 with P A1/O4/O3 -RBSII- gfpmut3* and Km-resistance gene on pJBA28 ( 54 ) was introduced into plasmid pSN0729-62 ( 5 ) using E. coli S17-1λ pir ( 55 ) as described previously ( 56 ). For pSN1104-11 gfp Tc, P A1/O4/O3 -RBSII- gfpmut3* on pJBA28 were introduced into the plasmid by homologous recombination (Text S1).…”
Section: Methodsmentioning
confidence: 99%
“…A mini-Tn 5 with P A1/O4/O3 -RBSII- gfpmut3* and Km-resistance gene on pJBA28 ( 54 ) was introduced into plasmid pSN0729-62 ( 5 ) using E. coli S17-1λ pir ( 55 ) as described previously ( 56 ). For pSN1104-11 gfp Tc, P A1/O4/O3 -RBSII- gfpmut3* on pJBA28 were introduced into the plasmid by homologous recombination (Text S1).…”
Section: Methodsmentioning
confidence: 99%
“…This result highlights that conjugal transfer occurs in the field. Plasmid pSN1216-29 has been isolated from cow manure [114] and was demonstrated to be able to conjugate with a broad range of bacterial genera extracted from soil and cow manure [115]; despite the fact that this plasmid does not carry accessory genes, one transposition event can lead to antimicrobial resistance acquisition, followed by horizontal dissemination.…”
Section: Args Spread By Hgt Mechanismsmentioning
confidence: 99%
“…The four PromA plasmids (pSN1104-11, pSN0729-62 [30], pMH0613-68, and pYK0414-12) were transferred to P. resinovorans CA10rm4R fromCA10dm4RGFP with pBBRMCS-2 [30]. Then mini-Tn5 (3 859 bp) with P A1/O4/O3 -RBSII-gfpmut3* and the Km-resistance gene was randomly inserted into the four PromA plasmids using pJBA28 [33] and E. coli S17-1 λpir [34] as described previously [17]. The mini-Tn5 was inserted into 38 362 nucleotides (nt) of pSN1104-11, 40 891 nt of pMH0613-68, 35 137 nt of pYK0414-12, and 35 612 nt of pSN0729-62.…”
Section: Construction Of Gfp-tagged Plasmidsmentioning
confidence: 99%
“…These plasmid host ranges are determined using filter and/or liquid mating assays between donor strain(s) and recipients (transconjugant ranges). Several studies have comprehensively identified the transconjugants of plasmids including members of IncP/P-1 [5][6][7][8][9][10][11][12], IncP-7 [13], IncP-9 [13], IncH1A [14], IncQ/P-4 [15], PromA (only PromAβ−1) [16], and pSN1216-29 [17]. However, the number of plasmids whose host ranges have been analysed is still limited because the analyses are timeconsuming and costly, and it is unfeasible to experimentally identify all plasmid transconjugant ranges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation